Dampak Berita Hoax pada Masyarakat: Studi Fenomenologi Kelurahan Ngronggo Kota Kediri - Nila Septiana; Marcelino Wahyu R (Ngarsa: Journal of Dedication Based on Local Wisdom, 2021)
Hoax news during a pandemic like this very often circulates among the public. Its impact also cannot be underestimated. Because people who should receive accurate and fact-based information at this time, become receptive to artificial and uncertain information, so that in this study researchers will discuss the process of spreading hoax news and its impact on society. In which the researchers took the object of research, namely the Ngronggo village community, Kediri city. As for the data collection method, the researcher uses a phenomenological approach where this approach is used to examine a situation that is happening in the community. And also the analytical method used for researchers using descriptive qualitative methods, which this method will explain how things are in the community when there is hoax news circulating. The researchers will analyze the source of the data obtained with communication theories so that they can better explain how the process of spreading hoax news and the impact of the hoax news. The results of the research itself reveal that the spread of hoax news itself is a noise in Shanon and Weaver's communication theory which in every process of delivering information there will be noise or interference on the channel or media used to convey information. And also the impact caused by the hoax news will lead to the swaying of public opinion and also anxiety that occurs in the community so that it will cause disturbance and noise in the surrounding social environment.